ANALYSIS OF LABOUR-INTENSIVE MICROENTREPRISES USING THE COBB-DOUGLAS PRODUCTION FUNCTION: INSIGHTS FROM MICROENTREPRISES IN WEST NUSA TENGGARA: - Budiman; M Jumaedi; Safitri, Dhanny; Kuntary Ibrahim, Isra Dewi (Universitas Mataram, 2025)
Microenterprises in Indonesia play a significant role in regional employment creation and economic development. However, many run under their productive potential due to constraints in technology provision, labor management, and scaling strategies. This study assesses four labor-intensive microenterprises in West Nusa Tenggara (NTB) using a qualitative case study approach, supported by Cobb-Douglas production function modelling. Through in-depth field analysis of UD Batako Sejahtera, UD Muslim Kerupuk Kulit, UD Berkah Beton, and Artshop Kodong Sasak, we examine the relationship between labor, capital, and output, recognize forms of return to scale, and propose tailored strategies to enhance productivity. Findings revealed that most enterprises initially experience increasing returns to scale, yet they face inefficiencies beyond the origins of optimal input. Modest investments in relevant technology, structured work systems, and incentive programs can significantly increase output and sustainability.